Combined Influence of Metakaolin and Palm Oil Fuel Ash on the Heat of Hydration and Permeability of High Performance Concrete - Mansour, Mohammed; Ismail, Mohd Hanif; Wan Ibrahim, Mohd Haziman; Mokhtar, Norfaniza; Al Shalif, Abdullah Faisal (International Journal of Integrated Engineering, 2025)
Utilizing metakaolin (MK) and palm oil fuel ash (POFA) mitigates the negative impacts of high content cement in high performance concrete (HPC).  This research aims to investigate the heat of hydration (HOH) and water permeability of HPC blended with MK and POFA as cement substitutes. Three concrete mixtures namely a control made with 100% ordinary Portland cement (OPC), optimum MK; and optimum blend of MK and POFA were prepared. Subsequently, the temperature rise due to HOH and water permeability were evaluated. The results demonstrated that using 15% MK with or without 20% POFA reduced the peak temperature and coefficient of water permeability of HPC compared to control concrete. The findings suggest that incorporating MK and POFA in HPC is beneficial for mass concrete to prevent thermal cracking and for water-retaining structures to block permeable pores.